#TITLE_ALTERNATIVE# - ERIA RAHMATIKA (NIM 10704113); Pembimbing: Dr. Sukmadjaja Asyarie dan Dr. Heni Rachmawati, DESI
Ketoprofen is a poorly water-soluble drug has low bioavailability. The aim of this study is to observe influence of combination of cremophor RH 40 and PEG 6000 on ketoprofen solubility. Ketoprofen was mixed with cremophor RH 40 and PEG 6000 1:4 as carrier. The carrier was prepared by melting method at temperature 60oC. Physical mixture of ketoprofen-carrier characterized including solubility, infra red spectroscopy, XRPD, DSC and dissolution. Physical mixture of ketoprofen-carrier at ratio of 1:4 increased solubility of ketoprofen in water and at ratio of 1:5 in HCl pH 1.2, respectively 1.61 and 1.63 (P<0.05). Physical mixture of ketoprofen-carrier showed decreased melting temperature indicated by thermogram and the IR spectra showed interaction of ketoprofen and carrier. In addition, the disappearance of specific peaks of ketoprofen at XRPD diffractogram indicated any alteration in ketoprofen chrystallinity. Dissolution test of physical mixture ketoprofen-carrier in capsule in HCl pH 1.2 as medium showed increased of ketoprofen dissolved at 15 minutes (DP15) and 90 minutes (DP90) was respectively 44.66% and 98.72%. The physical mixture of PEG 6000 and cremophor RH 40 with ketoprofen showed physical interaction resulted in decreased melting temperature, alteration of ketoprofen chrystallinity and IR spectra. This interaction was suggested as a mechanism influencing improved solubility of ketoprofen.